2017
DOI: 10.1186/s12882-017-0794-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of nephrotoxicity of drugs of abuse, 2005–2016

Abstract: BackgroundThe United States is faced with an unprecedented epidemic of drug abuse. Every year thousands of Americans visit the emergency departments all over the country with illicit drug related complaints. These drugs have been known to be associated with a range of renal pathologies, from reversible acute kidney injuries to debilitating irreversible conditions like renal infarction. So far, no comprehensive study or systematic review has been published that includes the commonly used street drugs and design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 128 publications
0
27
0
5
Order By: Relevance
“…30 The use of illicit substances such as cocaine, heroin, or methamphetamine has also been linked with an increased risk for CKD progression and increased mortality risk among adults with established CKD. 105,106 Infections such as endocarditis, hepatitis B and C, and HIV also increase the risk factors for CKD. 10 Furthermore, heavy metal pollutants (e.g., arsenic, cadmium, lead, and mercury) and other environmental toxins have been shown to be harmful to the kidneys.…”
Section: Mitigation Of Nontraditional Risk Factors For Ckdmentioning
confidence: 99%
“…30 The use of illicit substances such as cocaine, heroin, or methamphetamine has also been linked with an increased risk for CKD progression and increased mortality risk among adults with established CKD. 105,106 Infections such as endocarditis, hepatitis B and C, and HIV also increase the risk factors for CKD. 10 Furthermore, heavy metal pollutants (e.g., arsenic, cadmium, lead, and mercury) and other environmental toxins have been shown to be harmful to the kidneys.…”
Section: Mitigation Of Nontraditional Risk Factors For Ckdmentioning
confidence: 99%
“…In a systematic review of nephrotoxicities related to drugs of abuse, cocaine use was associated with an elevated risk of rhabdomyolysis and ischemic nephropathy. 26 Ongoing monitoring of renal function as recommended by PrEP clinical guidelines is warranted, but more intensive renal monitoring with concomitant stimulant use does not seem indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine use is associated with glomerular, tubular, vascular, and interstitial damage, and can precipitate acute kidney injury. [23][24][25][26] To address these gaps in the literature, we assessed the associations of biologically confirmed cocaine use with PrEP adherence (assessed objectively via a pharmacologic measure), PrEP care engagement, and renal function in the iPrEx open label extension (OLE).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent reviews of nephrotoxicity from illicit drugs have found some evidence of direct nephrotoxicity. Where kidney biopsies have been available, renal injury other than acute tubular necrosis have included acute interstitial nephritis and glomerulonephritis as the commonest, but other findings include thrombotic microangiopathy (MDMA), vasculitis (MDMA, cocaine), vascular thrombosis or infarction (cocaine), and crystal nephropathy (heroin, cannabinoids) . The additional mechanisms of renal injury may explain why illicit drug users develop worse AKI even allowing for their higher CK.…”
Section: Discussionmentioning
confidence: 99%